Enhancing Brown Sugar Potential as Homemade Product Through Brand Image Enhancement Strategy - Jamalia, M.N; Akkas, Dahliana; Sauri, Muh. Sofyan; Mursalim, Nadila; Syuhri, Muhammad Fuad; Saini, Muh. Juhadi; Pujiastuti, Hesti (Lembaga Dongan Dosen, 2023)
This paper will provide an analysis of a workshop held in the Village of Maddenra with the intention of enhancing brown sugar farmers' marketing skills. The purpose of the workshop was to enhance the marketing skills of brown sugar farmers. The workshop was organized with the intention of holding it in the Maddenra Village in the future. As part of an effort to provide community service, the training focused on the utilization of technology in marketing endeavors and the demand for aesthetically appealing product packaging. In an endeavor to provide community service, this action was taken. This was accomplished as part of an initiative to conduct community service. As part of an initiative to contribute back to the community by performing volunteer work, training was provided. The program was greeted with enthusiasm, particularly from more experienced participants who were aware of social media's potential to enhance their level of commercial performance. This response was particularly favorable to the program being presented. The workshop also emphasized the importance of implementing marketing strategies that make use of social media and actively participating in community-beneficial activities in order to gain an advantage over one's competitors, the workshop serve its purpose as a solution to increase the number of buyer for this specific product. This was brought up as a means of gaining a competitive advantage. The results of this paper indicate that the use of technology and the possession of digital literacy skills are crucial for the growth and development of small and medium-sized enterprises (SMEs).